Política avaliativa do ENEM : pressupostos da qualidade social da educação? - Piaia, Karine (2013)
This thesis aims to analyze the educational public policy of High School evaluation (Enem), organized by the National Institute of Education and Research (INEP) - MEC. In this sense, it is fundamental to understand the building process of this evaluation proposal and unveil aspects about it. The political clashes, education conception and their purposes must be explanned, because the educational public policies are part of a broader project of society and human being. The discussion of the Evaluation and Quality can help with education proposals that, in fact, provide the learning and the social emancipation of the individuals involved in the educational process. Therefore, I emphasize that this study, while focusing on evaluation, it intends to motivate a critical reflection about its ability to function as educational quality improving. The most recurrent concepts explained are: Quality, State, Education Public Policy, Marketing Education, Neoliberalism, Emancipation, Regulation and Evaluation. These concepts helped me understand the totality and the contradictions about the educational subject. Also, it was possible to find and contextualize the governmental actions that gave support and started Enem with the theoretical support . I emphasize that the investigation of one of Enem Examinations, year 2011, in the Languages and Writing area, was done as a reference and studies complementation about the composition of the curricular and the theoretical foundations that support the exam. Therefore, the following question marks itself as a problem to be researched: the Evaluative Public policy that originated and supports the National High School Exam, does it support itself in the educational conception quality? More than to promise truths finished and judgments the evaluation must assume its political character and respect the contradictions and the pluralism, then it needs to be procedural and emancipatory that produces senseand manages the necessary changes. Saying this, I reaffirm that the research becomes a manner to question the reality in an attempt to intervene on her. Therefore, this study can contribute as an instrument of evaluative public policy analysis, as well as it can enhance anti-hegemonic pedagogical processes which coincide in the formulating of new evaluation parameters, and these ones can create improvements in the education quality in the view of the formation of the individual in his ontological emancipatory dimension